Effect of sintering temperature on the electrical properties of a nanocomposite electrolyte based on calcium-doped ceria/ternary carbonate - Amar, I. A.; M. Ahwidi, Mohammed; Zidan, Mohammed; Abdalsamed, Ihssin; Ali, Asmaa (Libyan Journal of Science &Technology, 2022)
In this study, the effect of sintering temperature on the proton-and oxygen-ion conductivities of a nanocomposite electrolyte based on Ca-doped ceria/carbonate was investigated. Ca-doped ceria (CDC) nanoparticles were successfully synthesised using a sol-gel process. Ternary carbonate eutectic salt ((Li/Na/K)2CO3) was prepared by solid-state reaction. A dual-phase nano composite was prepared by mixing CDC with the ternary carbonate at a weight ratio of 70:30. The prepared materials were characterised by X-ray diffraction (XRD) and thermal analysis (TGA-DSC). The fabricated green nanocomposite pellets were sintered at two different temperatures (600 and 700°C). AC Impedance spectroscopy was used to measure the ionic conductivities of the composite electrolyte within the range of temperature from 300 to 600°C. The proton ion (H+) conductivities at 600°C were found to be 0.33 and 0.37 S cm1 for samples sintered at 600 and 700°C, respectively. The oxygen ion (O2) conductivities at 600°C for samples sintered at 600 and 700°C were found to be 0.35 and 0.27 S cm1, respectively. The nanocomposite electrolyte was thermally stable in both atmospheres (oxidising and reducing). The results suggest that the nanocomposite can be used as an electrolyte material for the electrochemical devices operating within low to intermediate temperature range.